Management of Student with Special Needs in Inclusive Schools (Case Study in the State Junior High School 30 Surabaya and Alam Insan Mulia Junior High School Surabaya) - Nur Baiti, Rizka Rahma; Soedjarwo, Soedjarwo; Purbaningrum, Endang (Universitas Malikussaleh, 2021)
This study was conducted to determine the management of students with special needs in schools at State Junior High School 30 Surabaya and Alam Insan Mulia Junior High School Surabaya by paying attention to student management which includes: (a) student planning, (b) student coaching , (c) student evaluation and (d) student mutation. Based on the problems or case studies that occur, at State Junior High School 30 Surabaya and Alam Insan Mulia Junior High School Surabaya, the management of students with special needs has many problems such as a lack of cooperation between educators and inadequate management processes for students with special needs. The method used is qualitative research, with a type of case study because it aims to obtain in-depth data and information so that the aim is to determine the implementation of management for students with special needs. The subjects of this study were the principal, deputy principal of student affairs, school teachers, coordinator of inclusion, teachers and homeroom teachers as well as most students with special needs from each school. Data collection techniques using observation, interviews, and documentation. The data analysis technique used in this study was an interactive analysis model consisting of three components, namely data condensation, data triangulation, data presentation and conclusion drawing.The results of research obtained at State Junior High School 30 Surabaya and Alam Insan Mulia Junior High School Surabaya show that the management of students carried out is mostly in accordance with the indicators in this study. The planning, coaching, evaluation and transfer processes are carried out in accordance with the procedures, vision and mission of the school and regulations of the education office. The inhibiting factors found were the lack of communication and cooperation between teachers, student coordinators with special needs and parents. This research is expected to be useful for researchers studying the field of inclusion and student management.